The Creative Destruction of Montreal: Street Widenings and Urban (Re)Development in the Nineteenth Century - Gilliland, Jason (Urban History Review / Revue d'histoire urbaine, 2002)
Rapid industrialization of North American cities during the nineteenth century was associated with periodic innovations in transportation and massive increases in traffic, which, in turn, caused perennial problems of congestion in ill-adapted urban cores. During the latter half of the nineteenth century, the municipal government of Montreal expropriated and destroyed thousands of properties to widen dozens of existing streets. This paper argues that the key to these acts of "creative destruction" was the removal of barriers to circulation through a periodic redimensioning of the "urban vascular system, " and hence, a speed up in the rate of urban growth. A detailed investigation of the planning and execution of major street widening projects between 1862 and 1900 reveals how the built environment of Montreal was periodically destroyed and recreated by a local growth coalition committed to increasing aggregate rents, property values, and municipal revenues, through the intensification of land use. Examination of a sample of properties before and after street widenings suggests that redevelopment was most intense during economic boom periods and in central areas, when and where competition for space was most extreme, and there existed the greatest pressure to remodel the built landscape to fit the needs of a changed economic environment.